New names in Aralia (Araliaceae), living and fossil - Doweld, Alexander B. (Phytotaxa, 2017)
The nomenclature of some fossil and extant homonymic species of Aralia is resolved. Aralia laevis J. Wen (extant) is replaced by a new name A. indonesica nom. nov., because of earlier homonym, A. laevis E.M.Reid (fossil). Aralia debilis J. Wen is rehabilitated as a legitimate substitute to the later homonym, A. elegans Ho, due to the existence of several earlier homonyms, the extant A. elegans Linden ex Koch, A. elegans Cunn. ex W.Hill and A. elegans Hort. ex Saporta, and the fossil A. elegans Velenovský. Additional four new replacement names are proposed for fossil species based on endocarp remains from the Miocene sediments of Siberia: Aralia asiatica nom. nov. for A. rugosa Dorofeev non Blume, A. mammuthica nom. nov. for A. dubia V.P. Nikitin non Sprengel nec Fontaine, A. borealis nom. nov. for A. tertiaria Dorofeev non Pilar, and A. tobolica nom. nov. for A. lucida Dorofeev non Hasskarl. The later homonym A. angustiloba Kolakovsky non Lesquereux, based on the fossil foliage from the Pliocene sediments of Transcaucasus, is transferred into Brassaiopsis as B. kolakovskyana nom. nov. Fossil species A. furcata, described on the basis of leaf remains from the Upper Cretaceous (Cenomanian) of Bohemia, is transferred into Haliserites as H. furcatus comb. nov. The fossil later homonym A. serrata Knowlton non Saporta, described on the basis of leaf remains from the Palaeocene of North America, is transferred into Platanus as P. serrata nom. nov.